Exploring South Africa's hidden marine parasite diversity: two new marine Ergasilus species (Copepoda: Cyclopoida: Ergasilidae) from the Evileye blaasop, Amblyrhynchote honckenii (Bloch) - Linda van der Spuy; Rodrigo B. Narciso; Kerry A. Hadfield; Victor Wepener; Nico J. Smit (Parasitology)
Marine parasites remain understudied in South Africa with little information available on their diversity and the effects these parasites may have on their hosts. This is especially true for parasitic copepods within the family Ergasilidae. Among the 4 genera known in Africa, Ergasilus Nordmann, 1832 is the most speciose with 19 reported species. However, this represents only 12% (19/163) of the global diversity. Furthermore, only 5 known African species are reported from marine environments, and only 1 is reported from the South African coastline. Given the rich biodiversity along this coastline, a high marine parasite diversity could be expected from these shores. As a case study, the Evileye blaasop, Amblyrhynchote honckenii (Bloch), a marine and brackish fish species, was screened for parasites along the South African coastline. This resulted in the discovery of 2 species of Ergasilus new to science (Ergasilus arenalbus n. sp. and Ergasilus chintensis n. sp.), which makes them the second and third ergasilid species reported for tetraodontid pufferfishes worldwide. Although genetically distinct, the 2 newly described species clustered in the same subclade within the Ergasilidae based on 18S rDNA, 28S rDNA and COI mtDNA phylogenies. The newly described species differ morphologically from each other, and their respective congeners based on the size and armature of the antenna; body segmentation; and general ornamentation throughout the entire body. The addition of these 2 new species from a single host species indicates that South Africa's marine fishes contain most probably a hidden parasitic copepod diversity that is worth exploring.